Investigation of mechanical properties of welded aluminium alloys - Addy Firdaus, Omar (2012)
This thesis will study about the current and the filler to the properties of the welding joint. The strength of the joint depends on the composition inside the weld zone. Welding process using filler gives the different value of strength compare to welding that does not use filler. In this study, tungsten inert gas (TIG) welding process applies by welding AA6061 aluminium alloys sheet. The welding process used by using the different value of current which is 30, 40, 50, 60 and 70A. Two types of filler material, ER4043 and ER4047 are the filler that used with same value of current. Hence, the mechanical properties were investigated when mechanical testing occurs such as tensile test and hardness test. Hardness value (HV) by using current 40A and filler type ER4047 give the value of 26.7 HV at the center of the weld zone, which is the highest value compare to others. Since hardness are directly proportional to the tensile strength, the value of ultimate tensile strength (UTS) by using 40A and filler type ER4047 give the value of 93.79520MPa. Hence, by using 40A and filler type ER4047 gives the strength of the joint compare to others.